An ATP-Binding Cassette Transporter and Two rRNA Methyltransferases Are Involved in Resistance to Avilamycin in the Producer Organism Streptomyces viridochromogenes Tü57 - Weitnauer, Gabriele (American Society for Microbiology, 2001)
Three different resistance factors from the avilamycin biosynthetic gene cluster of Streptomyces viridochromogenes Tü57, which confer avilamycin resistance when expressed in Streptomyces lividans TK66, were isolated. Analysis of the deduced amino acid sequences showed that AviABC1 is similar to a large family of ATP-binding transporter proteins and that AviABC2 resembles hydrophobic transmembrane proteins known to act jointly with the ATP-binding proteins. The deduced amino acid sequence of aviRb showed similarity to those of other rRNA methyltransferases, and AviRa did not resemble any protein in the databases. Independent expression in S. lividans TK66 of aviABC1 plus aviABC2, aviRa, or aviRb conferred different levels of resistance to avilamycin: 5, 10, or 250 μg/ml, respectively. When either aviRa plus aviRb or aviRa plus aviRb plus aviABC1 plus aviABC2 was coexpressed in S. lividans TK66, avilamycin resistance levels reached more than 250 μg/ml. Avilamycin A inhibited poly(U)-directed polyphenylalanine synthesis in an in vitro system using ribosomes of S. lividans TK66(pUWL201) (GWO), S. lividans TK66(pUWL201-Ra) (GWRa), or S. lividans TK66(pUWL201-Rb) (GWRb), whereas ribosomes of S. lividans TK66 containing pUWL201-Ra+Rb (GWRaRb) were highly resistant. aviRa and aviRb were expressed in Escherichia coli, and both enzymes were purified as fusion proteins to near homogeneity. Both enzymes showed rRNA methyltransferase activity using a mixture of 16S and 23S rRNAs from E. coli as the substrate. Coincubation experiments revealed that the enzymes methylate different positions of rRNA.